Impact of Paroxysmal Supraventricular Tachycardia on Pregnancy Outcomes - Arya Ardehali, BSc; Marla Kiess, MD, FRCPC; Valerie Rychel, MD, FRCSC; Amanda Barlow, MD, FRCPC; Jennifer Oakes, MD, FRCSC; Marc Deyell, MD, FHRS; Jasmine Grewal, MD, FRCPC (CJC Open)
Background: Paroxysmal supraventricular tachycardia (PSVT) is one of the most common arrhythmias in pregnant women. However, studies investigating the risk of PSVT in pregnancy are lacking. In pregnancy, we aimed to determine the (1) proportion of women presenting with new-onset PSVT, (2) impact of prior PSVT history on episode severity and management, and (3) rate of adverse maternal and fetal or neonatal outcomes associated with PSVT. Methods: Retrospective case-control study: 77 consecutive pregnancies in 75 women referred to the St Paul’s Hospital Cardiac Obstetrics Clinic (2010-2022) with a history or new presentation of PSVT. Maternal obstetric and fetal or neonatal adverse outcomes were compared to a healthy control group. Results: Sixty-three pregnancies (82%) had a history of PSVT and 14 (18%) were new-onset in pregnancy. Sixty-eight percent of those with PSVT history had recurrence in pregnancy. Women with a recent history of PSVT within 5 years of pregnancy were more likely to experience recurrence than women with a remote history (81% vs 31%, P < 0.001). This group also experienced more frequent PSVT during pregnancy and increased rates of chemical cardioversion (38% vs 13%, P = 0.05). There were similar rates of adverse obstetric (8% vs 2%, P = 0.24) and fetal or neonatal outcomes (17% vs 19%, P = 0.72) between the PSVT group and controls. Conclusions: PSVT events were safely managed in pregnancy with similar obstetric and fetal or neonatal outcomes as controls. However, recurrence of PSVT during pregnancy is frequent and leads to management complexities among those with a history, reinforcing the need for pre-pregnancy counselling and catheter ablation for definitive management. Résumé: Contexte: La tachycardie paroxystique supraventriculaire (TPSV) est l’un des types d’arythmie les plus fréquents chez les femmes enceintes. Il existe toutefois un manque flagrant d’études portant sur le risque de TPSV pendant la grossesse. Dans cette optique, nous voulions déterminer dans les cas de grossesse : 1) la proportion de femmes qui consultent pour une TPSV d’apparition nouvelle, 2) l’effet des antécédents de TPSV sur la sévérité des épisodes et leur prise en charge et 3) les taux d’issues défavorables pour la mère et le fœtus ou le nouveau-né associés à la TPSV. Méthodologie: Étude cas-témoin rétrospective : 77 grossesses consécutives chez 75 femmes orientées vers la clinique de cardio-obstétrique de l’hôpital St Paul (2010-2022) présentant des antécédents de TPSV ou une TPSV d’apparition nouvelle. Les issues défavorables pour la mère et le fœtus ou le nouveau-né ont été comparées à celles d’un groupe témoin en bonne santé. Résultats: Soixante-trois femmes (82 %) présentaient des antécédents de TPSV et 14 (18 %) présentaient une TPSV d’apparition nouvelle pendant la grossesse. Il y a eu récurrence de la TPSV pendant la grossesse chez 68 % des femmes ayant des antécédents. Les patientes qui avaient subi une TPSV au cours des 5 années précédant la grossesse étaient plus susceptibles de connaître une récurrence que celles dont la TPSV était plus éloignée dans le temps (81 % vs 31 %, p < 0,001). Les épisodes de TPSV pendant la grossesse étaient également plus fréquents chez les premières tout comme la cardioversion pharmacologique (38 % vs 13 %, p = 0,05). Les taux des issues obstétriques (8 % vs 2 %, p = 0,24) et fœtales ou néonatales (17 % vs 19 %, p = 0,72) défavorables étaient similaires entre les groupes TPSV et témoin. Conclusions: Les épisodes de TPSV ont été pris en charge en toute sécurité pendant la grossesse avec des issues obstétriques et fœtales ou néonatales comparables à celles observées dans le groupe témoin. Cependant, la récurrence de la TPSV pendant la grossesse est fréquente et complique la prise en charge des femmes ayant des antécédents, d’où la nécessité de bien conseiller les patientes avant la grossesse et d’envisager l’ablation par cathéter comme traitement définitif.